Women Empowerment Through Engineering Education: A Bibliometric Review - Bagane, Pooja Anil; Gaurvadkar, Amey (Journal of Engineering Education Transformations, 2025)
Academia and Industries are facing a problem of lack of diversity, precisely gender diversity. We investigated a review of extant literature and macro data on gender equality in both Academia and Industry. To reduce the gender gap an initiative must have been taken to encourage women in the involvement in the education field. The primary purpose of this bibliometric survey is to determine the scope of the literature available for women’s empowerment through engineering education. The commemorative analysis is based on Scopus because it provides research databases from various fields and tools such as Sciencescape and Gephi. In the theoretical survey, we analyze the prominent publications of journals, conferences, and the majority from the United States. The set of data from the time series has begun since 2004 until today. Most research publications are in the field of social science scope, followed by engineering and computer science.